Manipulative orthopedic therapy for chronic spinal pain: a systematic review - Marcondes, Freddy Beretta; Lodovichi, Samuel Satraceri; Cera, Milton (Acta Fisiátrica, 2010)
Objective: To examine the effectiveness of Manipulative Orthopedic Therapy (MOT) in cases of Chronic Vertebral Pain. Methods: A systematic search was performed in PEDro, Medline, and Science Direct databases in June 2010, retrieving recent randomized clinical trials that documented the effects of MOT in Chronic Vertebral Pain. Results: Eight articles about chronic cervical pain and eleven articles about chronic low back pain were reviewed. On chronic cervical pain, six papers showed that MOT associated with exercises was effective, maintaining the improvement of symptoms for up to 24 months. One study showed that MOT (with no exercises) was better than massage and another study showed that MOT provided immediate pain relief. In chronic low back pain, five clinical trials showed that MOT associated with exercises was effective in the short and long term; two papers showed that MOT was more effective than analgesics and anti-inflammatory drugs. Three studies showed that MOT is effective as a single treatment and one study showed that MOT is no more effective than stretching exercises. Conclusion: The MOT techniques (except osteopathy) are effective remedies in cases of chronic spinal pain. However, its effects in reduction of pain occur only in the short term and the combination of therapeutic exercises is needed for an effective long term result. More studies should be made to compare different MOT techniques and different exercise techniques with each other in cases of chronic spinal pain.